Analysis of The Completeness of Shipyard Facilities at PT. X - Pabian, Dwi Aura; Tuty Alawiah; Brilliant Hanief ageng; Muhammad Alfalah; Ma'ruf (LPPM AKMI SUAKA BAHARI CIREBON, 2025)
Ports are key infrastructure in maritime trade and transportation activities that play a vital role in facilitating the flow of goods and ships and in supporting economic growth and regional prosperity. PT. X, as a shipyard company, has a strategic interest in ensuring complete and efficient port facilities to support its operations. This study aims to analyze the completeness of port facilities at PT. X with the aim of increasing operational efficiency and improving overall port performance. This research approach uses a qualitative descriptive method with data collection techniques through observation, interviews, and document studies. Primary data were obtained through direct observation at PT. X and interviews with employees of the port facilities and the infrastructure department. While secondary data were obtained through literature studies from related articles, journals, and books. The results of the analysis show that PT. X has various important facilities such as docks, workshops, warehouses, offices, and functional facilities. Although most of the facilities are in good condition and have been utilized, some facilities are damaged or in poor condition that require further maintenance. This study provides an in-depth understanding of the importance of port facility analysis in improving operational efficiency and overall port performance and provides recommendations for necessary repairs and maintenance. Thus, the port can be more effective in supporting Port Operations.